2017
DOI: 10.1016/j.jdiacomp.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Incretin treatment and atherosclerotic plaque stability: Role of adiponectin/APPL1 signaling pathway

Abstract: Our findings suggest a potential role of adiponectin/APPL1 signaling in mediating the effect of incretin in the prevention of atherosclerosis progression or plaque vulnerability in T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…13 Moreover, a study conducted on patients showed that incretin treatment, via adiponectin/APPL1 signaling pathway, prevents atherosclerosis progression or plaque vulnerability in type 2 diabetes patients. 14 More intriguing, recent studies demonstrated that exendin-4 (also known as exenatide), a GLP-1R agonist, regulates the expression of extracellular-superoxide dismutase (EC-SOD), in A549 cells, by reducing DNMTs activity with consequently DNA demethylation in the EC-SOD promoter region. 15 Furthermore, in animal model of type 2 diabetes, exendin-4 treatment in the new-born period reversed the aberrant epigenetic modifications at pancreatic and duodenal home box 1 (Pdx1) promoter in intrauterine growth restriction (IUGR) islets preventing the development of diabetes in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, a study conducted on patients showed that incretin treatment, via adiponectin/APPL1 signaling pathway, prevents atherosclerosis progression or plaque vulnerability in type 2 diabetes patients. 14 More intriguing, recent studies demonstrated that exendin-4 (also known as exenatide), a GLP-1R agonist, regulates the expression of extracellular-superoxide dismutase (EC-SOD), in A549 cells, by reducing DNMTs activity with consequently DNA demethylation in the EC-SOD promoter region. 15 Furthermore, in animal model of type 2 diabetes, exendin-4 treatment in the new-born period reversed the aberrant epigenetic modifications at pancreatic and duodenal home box 1 (Pdx1) promoter in intrauterine growth restriction (IUGR) islets preventing the development of diabetes in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Although APPL1 is known to be an adaptor in multiple signaling pathways, phenotypic manifestations of its variants remain elusive. It is known that adiponectin has an antiatherosclerotic effect [ 36 ]. In atherosclerotic plaques of patients with T2DM, APPL1 is underexpressed relative to patients without diabetes [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, atherosclerotic plaques of T2DM patients showed lower levels of adiponectin and adaptor protein PH domain and leucine zipper containing 1 (APPL1), an adaptor protein that interact directly with adiponectin receptors, compared with non-diabetic patients. It was also shown that current incretin-users presented higher adiponectin and APPL1 content compared with never incretin users [ 37 ]. These findings suggest a potential role of adiponectin/APPL1 signaling mediating the beneficial effect of sitagliptin on the tissue characteristic of the carotid arterial wall.…”
Section: Discussionmentioning
confidence: 99%